Obligatoriness challenged: Who leaves whom? School's exclusion of young people in vulnerable conditions - Nora Gluz; Inés Rodríguez Moyano (Arizona State University, 2018)
At the turn of the last century, Argentina, like other Latin-American countries, began a political process with governments characterised as "new sign governments," tending to increase the value of policy against the market's "invisible hand" and making progress in the expansion of rights ensuring the access to social protection to groups that have been historically excluded from them. The so-called "kirchnerista" period (2003-2015), which starred on that stage in Argentina, was distinguished by putting up new regulations on the educational field aimed at expanding schooling through interventions that sustained state responsibility regarding new school publics' trajectories that had to be included by law in secondary level (National Education Law 26.206). Although the legislative advances and policies that accompanied that process were significant public efforts towards the achievement of that right, the available measures have not managed to challenge a sector of young people in a situation of extreme social vulnerability who are outside the school system and, many of them also, outside the social protection systems reoriented in the last stage of these governments. In this article we discuss how the official categories that account for this phenomenon are insufficient to understand the complex problem of school exclusion, and therefore, to build appropriate alternatives of action for these population groups. The empirical source stemmed from the research results on the so-called "inclusion policies" in secondary schools. Developed during the years 2014 and 2015 in the province of Buenos Aires, these policies entailed an extensive set of measures aimed at improving the integration process for the so-called '"new secondary school'" through devices to youth groups who had not completed compulsory education. This article presents an analysis, from the perspective of young people excluded from the access to school, of the processes leading to that situation and the capacity of the current policies to intervene.